EFL Pre-Service Teachers' High Inclusive Awareness: Researching Practical Implementation - Emaliana, Ive; Nur Lathifah, Egi; Iswahyuni; Husna, Lailatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The number of students with disabilities registering to study in Indonesia is expected to increase by 2024. This means that teachers need to know about inclusive education, especially this research will focus on prospective English teachers. Therefore, this study investigates the attitudes of prospective English teachers towards Inclusive Education, their determination to teach inclusive classes, and the implications for teaching practice. This research aims to identify factors that influence the understanding and implementation of inclusivity, explore teachers' practical experiences in creating an inclusive learning environment, and evaluate the effectiveness of the strategies used. This research uses a combined research method with explanatory sequential design. 100 prospective English teachers from several universities in Indonesia were involved as participants to answer the questionnaire. The questionnaire contains 17 questions. Quantitative data was analyzed using SPSS version 25 to determine the average value and correlation between attitude and determination. The results showed that prospective English teachers had high average scores in attitude and determination. However, the interview results showed that they had doubts about teaching in inclusion classes due to lack of preparation. This study shows that despite their positive attitude and determination, these prospective teachers would benefit from professional development courses and programs to better prepare themselves to teach in inclusion classes, which would reduce their doubts. The implications of this research can provide insight for educational policy makers in designing curricula that support the implementation of the principle of inclusivity in schools.